2005
DOI: 10.1186/bf03351822
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ground- and satellite-based airglow observations of geomagnetic conjugate plasma bubbles in the equatorial anomaly

Abstract: We compare, for the first time, geomagnetically-conjugate plasma bubbles observed by ground-based OI 630.0-nm all-sky imagers at Shigaraki, Japan (34.8• N, 136.1 • E; magnetic latitude 25.4• N) and Darwin, Australia (12.4• S, 131.0 • E; magnetic latitude 22.0 • S), with global-scale plasma structures (∼10,000 km in longitude) in the equatorial anomaly simultaneously detected with an OI 135.6-nm imager on the IMAGE satellite at ∼7 earth radii. As found previously, global-scale plasma structures in both hemisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Makela and Kelley (2003) proposed another technique to estimate plasma-bubble occurrence location, with composite airglow images from the ground, and showed a case study with bubbles separated by several hundred kilometers. Ogawa et al (2005) showed that plasma bubbles observed with an airglow imager on the ground were embedded in the crest of the 1000-km scale plasma density structure in the equatorial anomaly measured by the IM-AGE satellite. Tsunoda (2005) pointed out the importance of the large-scale wave structure in the bottomside F-region for day-to-day variability of ESF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Makela and Kelley (2003) proposed another technique to estimate plasma-bubble occurrence location, with composite airglow images from the ground, and showed a case study with bubbles separated by several hundred kilometers. Ogawa et al (2005) showed that plasma bubbles observed with an airglow imager on the ground were embedded in the crest of the 1000-km scale plasma density structure in the equatorial anomaly measured by the IM-AGE satellite. Tsunoda (2005) pointed out the importance of the large-scale wave structure in the bottomside F-region for day-to-day variability of ESF.…”
Section: Discussionmentioning
confidence: 99%
“…Oya et al, 1986;Eccles, 2004). Recent ground-and satellite-based airglow observations have also been a powerful technique to detect the zonal structure of the equatorial and low-latitude F-regions (e.g., Ogawa et al, 2005). Kelley et al (1981) and Hysell et al (1990) concluded that the large-scale modulation is partially due to spatially resonant atmospheric gravity waves (Beer, 1973), and then the seeded perturbation is amplified by the RayleighTaylor instability.…”
Section: Introductionmentioning
confidence: 99%
“…Makela et al (2006) showed the development of a secondary instability at the eastern wall of the plasma bubbles by using an airglow imager in Hawaii. Conjugacy of plasma bubbles along the geomagnetic field line has been confirmed using airglow imagers operated simultaneously in the northern and southern hemispheres Ogawa et al 2005;Martinis and Mendillo, 2007;Abdu et al 2009). Shiokawa et al (2004) showed that the conjugacy is maintained even during the growth phase of the plasma bubbles toward higher latitudes.…”
Section: Introductionmentioning
confidence: 97%
“…Gravity waves can produce a sinusoidal oscillation of the altitude of the bottomside of the F-region (Singh et al, 1997). Ogawa et al (2005) found wavy plasma structures (a few hundreds to 1000 km across) within the northern and southern equatorial anomaly crest. Gravity waves are considered to play an important role in the seeding process of plasma bubbles.…”
Section: Relation With Ionospheric Variabilitymentioning
confidence: 99%